TA'DIB EDUCATION IN CHARACTER DEVELOPMENT OF STUDENTS IN THE TIME OF COVID-19 - Nurul Anifah; Yunus Salik (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2021)
This study describes the concept of Ta'dib Muhammad Naquib Al-Attas in Character Development of Students. This research is a qualitative research that uses a pedagogical approach. The results show that the concept of Ta'dib according to Muhammad Naquib Al-Attas, the concept of Ta'dib emphasizes the mastery of the right knowledge in a person in order to produce stable charity and good behavior based on faith. The concept of Ta'dib, first, as a moral competence (morals) that must be possessed by educators and students, second, the formation of personality so that a person's psychological characteristics related to the tendency to relate socially with others, especially those related to; friendliness, self-control, implementation can be said to be successful because of the adab education that is applied in the lives of students, but it must also be admitted that during the epidemic of Ta'dib education there are few obstacles, such as education level, environment, culture, socio-economic level and online learning.